Evaluation of the outcome of linear stapler anastomosis in comparison to hand-sewn anastomosis in elective loop transverse colostomy closure in children: a study in a tertiary care hospital, Dhaka, Bangladesh - Ishad, Kaisar Yamin; Ul Huq, M. Ashraf; Hasina, Kaniz; Chawdhary, Nazmul Haider; Islam, M. Tawhidul; Islam, K. M. Shaiful (International Journal of Contemporary Pediatrics, 2023)
Background: Conventional hand suture technique of intestinal anastomosis has been in vogue for decades. Staplers which developed to simplify surgery began to have significant impact. Objective were to see outcome of linear stapler anastomosis in comparison to hand-sewn anastomosis in elective loop transverse colostomy closure in children. Methods: This prospective interventional study was carried out in the department of pediatric surgery, Dhaka medical college hospital, Dhaka from January 2018 to December 2019 over a period of 2 years. Forty-seven patients who underwent loop transverse colostomy closure were included in this study. Patients were allocated by purposive sampling into two groups, group A (linear stapler anastomosis) and group B (hand-sewn anastomosis). Results: Mean age of the patients were 5.79±3.23 years and 4.21±3.13 years in linear stapler anastomosis group and hand-sewn anastomosis group respectively. Male to female ratio was 1.2:1 in linear stapler anastomosis group and 5.25:1 in hand-sewn anastomosis group. The mean duration of return of bowel movements (passage of flatus after surgery) in linear stapler method was 32.82±6.04 hours and in hand sewn method was 40.56±5.35 hours (p<0.05). Oral feeding was started earlier in patients who underwent linear stapler anastomosis (3.18±0.39 days), as compared to hand-sewn anastomosis (4.16±0.37 days) (p≤0.001). The mean cost in linear stapler method was Tk. 4072±158 and in hand sewn method was Tk. 1440±362. Anastomotic leakage was lower (4.5%) in linear stapler anastomosis than that in hand-sewn anastomosis (20.0%) (p>0.05). Conclusions: Stapling technique can be used safely and effectively as a part of modern Surgeon`s armory and one should be equally expert with stapler guns as with needle holders and sutures.